THE ABSENCE OF BANKS IS RIBA: A CRITICAL STUDY OF THE THOUGHTS OF THE FORMER EGYPTIAN MUFTI ALI GOMAA - Robbani, Shofa; Ningrum, Ifa Khoiria; Azizah, Imroatul (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
This research aimed to examine the former Egyptian mufti Ali Gomaa's argument that the absence of banks is the essence of riba. He theorized that the lack of banks was to blame for the inflation, just as riba can. In contrast, as we all know, the prohibition on riba is due to increased debt repayments. He went on to say that the mistake made by Muslim scholars in understanding bank interest as a form of riba was their dogmatic way of thinking, which equated money invested in bank financing with money owed. This study uses the arguments of former Egyptian mufti Ali Gomaa as primary and secondary sources to conduct critical research. In this case, the explanation is provided by a qualitative descriptive research design. Its purpose is to demonstrate the validity of former Egyptian mufti Ali Gomaa's argument for justifying that destroying the banks is equivalent to breeding riba. The study discovered that the statement by Egypt's Mufti Ali Gomaa was based on the bank's overall performance, specifically as an intermediary institution, where the bank's function is as a financing institution rather than a lending institution. Also, unlike debts and credits, where profit-taking is forbidden, it is perfectly legal to do so in any funding. Ali Gomaa's statement is a unilateral claim because banks channel money to customers for various reasons, including financing, investment, and debt purposes. Research-based recommendations are offered for adjustments required by stakeholders. Optimistically, the submission of this study will trigger a positive response from stakeholders.